Prognostic significance of admission levels of troponin I in patients with acute ischaemic stroke. Issue 1 (16th December 2004) - Di Angelantonio, E; Fiorelli, M; Toni, D; Sacchetti, M L; Lorenzano, S; Falcou, A; Ciarla, M V; Suppa, M; Bonanni, L; Bertazzoni, G; Aguglia, F; Argentino, C
Abstract : Objectives: Successful prediction of cardiac complications early in the course of acute ischaemic stroke could have an impact on the clinical management. Markers of myocardial injury on admission deserve investigation as potential predictors of poor outcome from stroke. Methods: We prospectively investigated 330 consecutive patients with acute ischaemic stroke admitted to our emergency department based stroke unit. We analysed the association of baseline levels of cardiac troponin I (cTnI) with ( a ) all-cause mortality over a six month follow up, and ( b ) inhospital death or major non-fatal cardiac event (angina, myocardial infarction, or heart failure). Results: cTnI levels on admission were normal (lower than 0.10 ng/ml) in 277 patients (83.9%), low positive (0.10–0.39 ng/ml) in 35 (10.6%), and high positive (0.40 ng/ml or higher) in 18 (5.5%). Six month survival decreased significantly across the three groups (p<0.0001, log rank test for trend). On multivariate analysis, cTnI level was an independent predictor of mortality (low positive cTnI, hazard ratio (HR) 2.14; 95% CI 1.13 to 4.05; p = 0.01; and high positive cTnI, HR 2.47; 95% CI 1.22 to 5.02; p = 0.01), together with age and stroke severity. cTnI also predicted a higher risk of the combined endpoint "inhospital death or non-fatal cardiac event". Neither the adjustment for other potential confounders nor the adjustment for ECG changes and levels of CK-MB and myoglobin on admission altered these results. Conclusions: cTnI positivity on admission is an independent prognostic predictor in acute ischaemic stroke. Whether further evaluation and treatment of cTnI positive patients can reduce cardiac morbidity and mortality should be the focus of future research.